Aproximación teórica al fenómeno de la monoparentalidad - Méndez Fernández, Ana Belén; Leal Freire, Beatriz; Martínez Rodríguez, María (Acciones e Investigaciones Sociales, 2011)
Aproximación teórica al fenómeno de la monoparentalidad